If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + 3 = 2 Reorder the terms: 3 + 4n = 2 Solving 3 + 4n = 2 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4n = 2 + -3 Combine like terms: 3 + -3 = 0 0 + 4n = 2 + -3 4n = 2 + -3 Combine like terms: 2 + -3 = -1 4n = -1 Divide each side by '4'. n = -0.25 Simplifying n = -0.25
| 36x^2+24=-4 | | 6n+8=10 | | 9=-r-5+11 | | 64x^2+32x=-4 | | 3n+2=6 | | 8y^2+26y+21=0 | | 6x^2*6x^4= | | -9.24-2.436= | | 9y^2=-27y | | -3.9-(-0.35)+8.6-8= | | 3(5)+4y=125 | | 4t-8+20=5 | | 124x=24 | | 4+5.2X=-2.3X+7 | | Y=7-x | | 8x-(6x+4)=8 | | x+1-6=4 | | 0.8(x+300)=0.86x-198 | | 43-14p+7=-97 | | 8x+8=7x-9 | | 2x+4+6=22 | | x+(2x+6)=3 | | x+(2x+6)=10 | | -1(-1*X)=39 | | -1(-1xX)=39 | | 9x+12y-4x-6.2+30= | | 6x+x=252 | | 3x^3+17x^2-28x=0 | | -6x-11x=-68 | | -6x-11x=68 | | 220=40t | | b^2-12+36=0 |